2016
DOI: 10.1186/s12933-016-0442-1
|View full text |Cite
|
Sign up to set email alerts
|

Apocynin influence on oxidative stress and cardiac remodeling of spontaneously hypertensive rats with diabetes mellitus

Abstract: PurposeAlthough increased oxidative stress is a major component of diabetic hypertensive cardiomyopathy, research into the effects of antioxidants on cardiac remodeling remains scarce. The actions of antioxidant apocynin include inhibiting reactive oxygen species (ROS) generation by nicotinamide adenine dinucleotide phosphate (NADPH) oxidases and ROS scavenging. We evaluated the effects of apocynin on cardiac remodeling in spontaneously hypertensive rats (SHR) with diabetes mellitus (DM).MethodsMale SHR were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 92 publications
4
37
0
2
Order By: Relevance
“…The first echocardiographic analysis was performed at the 17th week of dietary treatment and evaluated every 2 months until the 41st week, totaling four moments of study (17,25,33, and 41 weeks). The analysis was performed using commercially available echocardiography (General Electric Medical Systems, Vivid S6, Tirat Carmel, Israel) equipped with a 5-11.5 MHz multi-frequency transducer, as previously described [22]. Rats were anesthetized by intraperitoneal injection of a mixture of ketamine (50 mg/kg) and xylazine (1 mg/kg).…”
Section: Echocardiographic Studymentioning
confidence: 99%
“…The first echocardiographic analysis was performed at the 17th week of dietary treatment and evaluated every 2 months until the 41st week, totaling four moments of study (17,25,33, and 41 weeks). The analysis was performed using commercially available echocardiography (General Electric Medical Systems, Vivid S6, Tirat Carmel, Israel) equipped with a 5-11.5 MHz multi-frequency transducer, as previously described [22]. Rats were anesthetized by intraperitoneal injection of a mixture of ketamine (50 mg/kg) and xylazine (1 mg/kg).…”
Section: Echocardiographic Studymentioning
confidence: 99%
“…Oxidative Stress and AGEs: AGEs, as the oxidative products, can induce OS, promote cell apoptosis, and fi nally induce both micro-and macro-vascular disease in diabetic patients [26,[54][55][56][57]. Direct cellular challenge with AGEs has been shown to cause OS in various cell types [58][59][60]. It is found that Schiffbase products and Amadori products themselves cause ROS production [61], while Nitric Oxide (NO) donors can scavenge free radicals and inhibit AGEs formation [62].…”
Section: Role Of Age In Dmmentioning
confidence: 99%
“…Rats were anesthetized by intramuscular injection of a mixture of ketamine (50 mg/kg) and xylazine (0.5 mg/kg). The cardiac structures were measured according to previous methods in an infarcted rat model [16][17][18]. Left ventricle end-diastolic dimension (LVDD), left ventricle end-systolic dimension (LVSD) and posterior wall thickness (LVWT) were measured at the maximal diastolic dimension, taken at the maximal anterior motion of the posterior wall.…”
Section: Echocardiographic Analysismentioning
confidence: 99%
“…LV systolic function was assessed by the following parameters: fractional shortening (FS) [(LVDD − LVSD) / LVDD] × 100, fractional area change (FAC) (DA − SA / DA × 100) and tissue Doppler imaging (TDI) of mitral annulus systolic velocity (S′). Diastolic function was evaluated by E wave deceleration time (EDT) assessed by pulsed wave Doppler and early diastolic mitral inflow velocities (E) and TDI of early mitral annulus diastolic velocity (E′) ratio (E/E′) [18].…”
Section: Echocardiographic Analysismentioning
confidence: 99%